Immunobiotic Lactobacillus jensenii TL2937 Alleviates Dextran Sodium Sulfate-Induced Colitis by Differentially Modulating the Transcriptomic Response of Intestinal Epithelial Cells - Sato, Nana; Garcia-Castillo, Valeria; Yuzawa, Mao; Islam, Md. Aminul; Albarracin, Leonardo; Tomokiyo, Mikado; Ikeda-Ohtsubo, Wakako; Garcia-Cancino, Apolinaria; Takahashi, Hideki; Villena, Julio; Kitazawa, Haruki (Frontiers in Immunology, 2020)
Immunobiotics have emerged as promising interventions to alleviate intestinal damage in inflammatory bowel disease (IBD). However, the beneficial properties of immunobiotics are strain dependent and therefore, each strain has to be evaluated in order to demonstrate its potential application in IBD. Our previous in vitro and in vivo studies demonstrated that Lactobacillus jensenii TL2937 attenuates gut acute inflammatory response triggered by Toll-like receptor 4 activation. However, its effect on colitis has not been evaluated before. In this work, we studied whether the TL2937 strain was able to protect against the development of colitis in a dextran sodium sulfate (DSS)-induced mouse model and we delved into the mechanisms of action by evaluating the effect of the immunobiotic bacteria on the transcriptomic response of DSS-challenged intestinal epithelial cells. L. jensenii TL2937 was administered to adult BALB/c mice before the induction of colitis by the administration of DSS. Colitis and the associated inflammatory response were evaluated for 14 days. Mice fed with L. jensenii TL2937 had lower disease activity index and alterations of colon length when compared to control mice. Reduced myeloperoxidase activity, lower production of pro-inflammatory and higher levels of immunoregulatory cytokines were found in the colon of TL2937-treated mice. In addition, the treatment of porcine intestinal epithelial (PIE) cells with L. jensenii TL2937 before DSS challenge differentially regulated the activation of the JNK pathway leading to an increase in epithelial cells integrity and to a differential immunotranscriptomic response. TL2937-treated PIE cells had a significant reduction in the expression of inflammatory cytokines, chemokines, adhesion molecules and other immune factors (NCF1, NCF2, NOS2, SAA2) when compared to control cells after the challenge with DSS. The findings of this work indicate that: a) L. jensenii TL2937 is able to alleviate DSS-induced colitis suggesting a potential novel application for this immunobiotic strain, b) the modulation of the transcriptomic response of intestinal epithelial cells would play a key role in the beneficial effects of the TL2937 strain on colitis, and c) the in vitro PIE cells immunoassay system could be of value for the screening and selection of new immunobiotic strains for their application in IBD.